Dengue Hemorrhagic Fever: Problems and Progress - Suchitra Nimmannitya (Indonesian Pediatric Society, 1975)
The paper represents a climcal reappraisal of dengue hemorrhagic fever (DHF) and the author’s purpose to briefly review and discuss the pertinent data obtained to date. The most frightening picture of DHF that clearly differentiates this new clinical entity from the classical dengue illness and contribute to its cause of death is the shock syndrome.